TINGKAT EFISIENSI USAHA TANI JERUK MANIS (CITRUS SP) NAGORI Pematang Purba, Kecamatan Purba, Kabupaten Simalungun, Provinsi Sumatera Utara - Asmina Herawaty Sinaga (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2022)
This study aims to : (1) determine the feasibility of technically and economically viable farming sweet orange (Citrus sp) in the study area, (2) determine the level of production and productivity of farming of sweet orange (Citrus sp) in the study area, (3) the effect use of production factors of labor, means of production, depreciation of equipment and land area to total production of sweet orange (Citrus sp) in the area of research, and (4) how the influence of socioeconomic factors (age, farming experience, education level and number of dependents) to the income of farmers sweet orange (Citrus sp) in the study area. The study was conducted in Nagori Pematang Purba, District Purba, Simalungun, North Sumatra Province. The results showed that the farming of sweet orange (Citrus sp) in the area of research worth the try in which the value of R / C of 2.96. The level of technical efficiency, the price of (allocative) and economic factors of farm production of sweet orange (Citrus sp) in the study area have not / not efficient. Farm production of sweet orange (Citrus sp) in the research area of 23 364 kg and the productivity is 31,152 kg / ha is still relatively low because it is still below the potential production of sweet orange (Citrus sp) at 57 tons / ha / year. Simultaneously labor costs (X1), the means of production (X2), depreciation of tools (X3) and land area (X4) significantly affects the production (Y) farming of sweet orange (Citrus sp) where the value of F (3.469) > F table (2 , 63) at the 95% confidence level. Partial variable labor (X1) positive effect but no significant impact on farm production of sweet orange (Citrus sp), while the means of production (X2) positive and significant impact, the depreciation of equipment (X3) and land area (X4) positive effect but not significant the farm production of sweet orange (Citrus sp). Simultaneously age (X1), education level (X2), farming experience (X3) and the number of dependents (X4) significant effect on income (Y) farming of sweet orange (Citrus sp) where the value of F (3.469) > F table (2 , 63) at 95% confidence level. Partially age variable (X1) positive effect but not significant to farm income of sweet orange (Citrus sp), while the level of education (X2) positive and significant impact on farm incomes sweet orange, farming experience (X3) is positive but not significant and the number of dependents (X4) has positive and significant effect on farm incomes sweet orange (Citrus sp).